EISCAT and Cluster observations in the vicinity of the dynamical polar cap boundary - A. T. Aikio; T. Pitkänen; D. Fontaine; I. Dandouras; O. Amm; A. Kozlovsky; A. Vaivdas; A. Fazakerley (Annales Geophysicae, 2008)
The dynamics of the polar cap boundary and auroral oval in the nightside ionosphere are studied during late expansion and recovery of a substorm from the region between Tromsø (66.6° cgmLat) and Longyearbyen (75.2° cgmLat) on 27 February 2004 by using the coordinated EISCAT incoherent scatter radar, MIRACLE magnetometer and Cluster satellite measurements. During the late substorm expansion/early recovery phase, the polar cap boundary (PCB) made zig-zag-type motion with amplitude of 2.5° cgmLat and period of about 30 min near magnetic midnight. We suggest that the poleward motions of the PCB were produced by bursts of enhanced reconnection at the near-Earth neutral line (NENL). The subsequent equatorward motions of the PCB would then represent the recovery of the merging line towards the equilibrium state (Cowley and Lockwood, 1992). The observed bursts of enhanced westward electrojet just equatorward of the polar cap boundary during poleward expansions were produced plausibly by particles accelerated in the vicinity of the neutral line and thus lend evidence to the Cowley-Lockwood paradigm. During the substorm recovery phase, the footpoints of the Cluster satellites at a geocentric distance of 4.4 R E mapped in the vicinity of EISCAT measurements. Cluster data indicate that outflow of H + and O + ions took place within the plasma sheet boundary layer (PSBL) as noted in some earlier studies as well. We show that in this case the PSBL corresponded to a region of enhanced electron temperature in the ionospheric F region. It is suggested that the ion outflow originates from the F region as a result of increased ambipolar diffusion. At higher altitudes, the ions could be further energized by waves, which at Cluster altitudes were observed as BBELF (broad band extra low frequency) fluctuations. The four-satellite configuration of Cluster revealed a sudden poleward expansion of the PSBL by 2° during ~5 min. The beginning of the poleward motion of the PCB was associated with an intensification of the downward FAC at the ...